Contextual Factors and Decision-Making in the Behavior of Finalization in the Positional Attack in Beach Handball: Differences by Gender Through Polar Coordinates Analysis - Vázquez-Diz, Juan A.; Morillo-Baro, Juan P.; Reigal, Rafael E.; Morales-Sánchez, Verónica; Hernández-Mendo, Antonio (Frontiers in Psychology, 2019)
The objective of this study was to analyze, within the framework of mixed methods, the relationship of the different contextual factors with the decisions shown in the end of the positional attack on beach handball. An analysis of polar coordinates, by gender, using as focal behaviors the simple and double objective, and the loss of possession of the attacking team, which are considered decisive to evaluate the success of the decisions at the end of the positional attack. These focal behaviours have been linked to criteria that characterise the attack situation such as minute, score, numerical balance, defensive system and duration. A total of 24 sessions were observed with the HOISAN computer software, using a tool designed ad hoc. The observation model used was punctual, multidimensional and nomothetic. The observation unit used for the positional attack from the time the specialist gains control of the game until possession changes. The results obtained showed that the advantage of the goals scored and the situations of numerical equilibrium of the teams significantly modulate the appropriate decision taken by both categories. However, they also indicated differences in the flow of matching behaviors for both categories in some respects. Specifically, it has been observed that increased attack duration in the female category has been significantly linked to successful performance, and the results also show that an elaborate attack is related to successful behaviors. In the men's category, it has been observed that the technical fouls committed by the attackers increase in the last minutes of the match. Likewise, as for the opposing defensive system, the results in the male category are related to successful behaviors before any of them; while in the female category, when playing against a defensive pressure system, the results are more related to errors during pass execution and reception. The use of polar coordinates for the estimation of the technical-tactical relations allows, from a psychological point of view, to determine the techniques and procedures of psychological intervention that optimize the action resources of the players individually and of the team as a group.